Phosphodiesterase 9A Inhibition Facilitates Corticostriatal Transmission in Wild-Type and Transgenic Rats That Model Huntington’s Disease - Chakroborty, Shreaya; Manfredsson, Fredric P.; Dec, Alexander M.; Campbell, Peter W.; Stutzmann, Grace E.; Beaumont, Vahri; West, Anthony R. (Frontiers in Neuroscience, 2020)
Huntington’s disease (HD) results from abnormal expansion in CAG trinucleotide repeats within the HD gene, a mutation which leads to degeneration of striatal medium-sized spiny neurons (MSNs), deficits in corticostriatal transmission, and loss of motor control. Recent studies also indicate that metabolism of cyclic nucleotides by phosphodiesterases (PDEs) is dysregulated in striatal networks in a manner linked to deficits in corticostriatal transmission. The current study assessed cortically-evoked firing in electrophysiologically-identified MSNs and fast-spiking interneurons (FSIs) in aged (9-11 months old) wild-type (WT) and BACHD transgenic rats (TG5) treated with vehicle or the selective PDE9A inhibitor PF-04447943. WT and TG5 rats were anesthetized with urethane and single-unit activity was isolated during low frequency electrical stimulation of the ipsilateral motor cortex. Compared to WT controls, MSNs recorded in TG5 animals exhibited decreased spike probability during cortical stimulation delivered at low to moderate stimulation intensities. Moreover, large increases in onset latency of cortically-evoked spikes and decreases in spike probability were observed in FSIs recorded in TG5 animals. Acute systemic administration of the PDE9A inhibitor PF-04447943 significantly decreased the onset latency of cortically-evoked spikes in MSNs recorded in WT and TG5 rats. PDE9A inhibition also increased the proportion of MSNs responding to cortical stimulation and reversed deficits in spike probability observed in TG5 rats. As PDE9A is a cGMP specific enzyme, drugs such as PF-04447943 which act to facilitate striatal cGMP signaling and glutamatergic corticostriatal transmission could be useful therapeutic agents for restoring striatal function and alleviating motor and cognitive symptoms associated with HD.